Within the Recent Indonesia Global Trade and Future Predictions: Data Analytic Approach - Priambodo, Aln Pujo (Cendekia Niaga, 2025)
International trade is directly calculated within Gross Domestic Product (GDP). The trade surplus is one of the pillars that is expected to have a significant impact on economic growth. In Indonesia, the trade balance has shown a surplus for the past few years, as indicated by the large exports compared to imports. However, its impact on economic growth is still debated. Based on export-import data from 2003 to 2023 and using a data analysis approach, this study found that there have been no changes in export and import commodities over years. The descriptive approach shows that raw materials are still dominated the exports, and Indonesia also continues to depend on other manufactured goods from international market. In addition, the Granger Causality approach shows a lag effect or delay from exports to economic growth. Although, optimism about the trade balance remains maintained, resulting from the Exponential Smoothing projection model for exports and Autoregressive Distributed Lag (ARDL) for imports, Indonesia still has challenges to overcome. Some steps that can be taken include strengthening domestic industrialization that prioritizes added value, downstreaming policies, adjustments to import and export tariffs, trade cooperation in ASEAN, regional economic integration, and infrastructure investment and strengthening human resources.